KAJIAN TENTANG PENURUNAN JUMLAH DONOR DARAH AKIBAT PANDEMI COVID-19: DATA SELAMA 4 TAHUN DARI UDD PMI KOTA PONTIANAK - Aditia, Aditia; Samwidya, Veronika Sriayu; Nuswantoro, Ari; Djohan, Herlinda; Supriyanto, Supriyanto; Reza, Nur (Media Penelitian dan Pengembangan Kesehatan, 2022)
The COVID-19 pandemic has left a noticeable mark on the health care sector. One such example is the blood services provided by the Blood Donor Unit (UDD) of Indonesian Red Cross (PMI). Every time there was an increase in COVID-19 cases, blood donation activities sharply decreased, according to the UDD PMI. During the COVID-19 pandemic, there was a scarcity of blood donors. This research aimed to see the difference in the number of blood donors before and during the pandemic. This research was descriptive analytical with a cross-sectional design by collecting data on the number of blood donors at UDD PMI Pontianak City from 2018 to 2022. The results of the study show that the number of blood donors before the pandemic was 52,607 donors, while the number of blood donors during the pandemic was 48,421 donors. which means there was a decrease in the number of blood donors by 4,186 donors (7.96%). The Independent Samples Test obtained a significant value of 0.045 (p < 0.05), which means there was a difference in the number of blood donors before and during the COVID-19 pandemic at UDD PMI Pontianak City. Concerns about the risk of infection and government policies limiting activities outside the home can explain why the COVID-19 pandemic has resulted in a decline in blood donation rates.